Outcomes in Clinically Relevant Patient Subgroups From the EMBRACA Study: Talazoparib vs Physician's Choice Standard-of-Care Chemotherapy. Issue 1 (21st October 2019) - Rugo, Hope S; Ettl, Johannes; Hurvitz, Sara A; Gonçalves, Anthony; Lee, Kyung-Hun; Fehrenbacher, Louis; Mina, Lida A; Diab, Sami; Woodward, Natasha E; Yerushalmi, Rinat; Goodwin, Annabel; Blum, Joanne L; et al.
Abstract: Background: Talazoparib is a poly(adenosine diphosphate-ribose) polymerase inhibitor that causes death in cells with breast cancer susceptibility gene 1 or 2 ( BRCA1/2 ) mutations. Methods: EMBRACA (NCT01945775) was a randomized phase III study comparing efficacy, safety, and patient-reported outcomes (PROs) of talazoparib (1 mg) with physician's choice of chemotherapy (PCT: capecitabine, eribulin, gemcitabine, vinorelbine) in locally advanced or metastatic breast cancer with a germline BRCA1/2 (g BRCA1/2 ) mutation. Prespecified patient subgroups were analyzed for progression-free survival, objective response, clinical benefit, duration of response, and safety. PROs were evaluated in hormone receptor-positive (HR+)/human epidermal growth factor receptor 2-negative (HER2−) or triple-negative breast cancer (TNBC) subgroups. Results: Of 431 patients, 287 were randomly assigned to talazoparib and 144 to PCT. Prespecified subgroup analyses showed prolonged progression-free survival with talazoparib (HR+/HER2−: hazard ratio = 0.47, 95% confidence interval = 0.32 to 0.71; TNBC: hazard ratio = 0.60, 95% confidence interval = 0.41 to 0.87) and greater objective response rate (odds ratio = 1.97 to 11.89), clinical benefit rate (odds ratio = 2.05 to 7.77), and duration of response with talazoparib in all subgroups. PROs in HR+/HER2− and TNBC subgroups showed consistent overall improvement and delay in time to definitive clinically meaningful deterioration with talazoparib vs PCT. Across subgroups, common adverse events included anemia, fatigue, and nausea with talazoparib and neutropenia, fatigue, and nausea with PCT. Seven patients (2.4%) receiving talazoparib had grade II alopecia and 22.7% had grade I alopecia. Conclusions: Across all patient subgroups with g BRCA -mutated advanced breast cancer, talazoparib demonstrated clinically significant superiority in outcomes compared with PCT.